Management and determination of hazardous occupational health and safety risks in recirculating aquaculture systems (RAS) - KARGA, Mustafa (Zenodo, 2024)
Responding to the increasing demand for protein consumption globally, the aquaculture sector continues to grow exponentially every day. Recirculating Aquaculture Systems (RAS) are advanced technology systems that provide sustainable fish farming opportunities by ensuring the efficient use of water resources. In addition, ornamental aquarium fish farming is also intensively carried out in RAS. There is a need for manpower to meet the increasing workload in RAS as well as in offshore aquaculture facilities. However, the working environment in RAS also brings with it various occupational health and safety (OHS) risks. The main hazards affecting occupational safety in these systems can be listed as chemical substance use, biological risks, electrical hazards, physical ergonomic difficulties and psychosocial working conditions. The aim of this study is to determine the OHS risks encountered in the RAS environment in Türkiye, based on 3 different enterprises, and to evaluate solution strategies for these risks and methods for creating a safe working environment. In the study, 3 different RAS were examined (A, B, C) and as a result of our study, it was seen that the risk assessment, emergency planning and employee training criteria were fully met in RAS workplaces where occupational health and safety specialist services were provided. Accordingly, it was determined that risk scores decreased in businesses employing occupational safety specialists. In addition, the total percentage risk score was calculated and it was shown that the total percentage risk score was lower in RAS with occupational safety specialists compared to the others.
Keywords: occupational health; Recirculating aquaculture; occupational safety; risk analyzes